Under Tension: Kinetochores and Basic Research. Issue 3 (7th July 2015) - Biggins, Sue
Abstract: The Genetics Society of America's Edward Novitski Prize recognizes an extraordinary level of creativity and intellectual ingenuity in the solution of significant problems in genetics research. The 2015 winner, Sue Biggins, has made significant contributions to our understanding of how chromosomes attach to the mitotic spindle, a process essential for cell division and frequently impaired in cancer. Among other achievements, Biggins was the first to demonstrate that the Aurora B protein kinase is a key regulator of kinetochore function and that chromatin composition and centromere identity can be regulated by histone proteolysis. In 2010, Biggins and her colleagues were the first to purify kinetochores and, using this system, have already made several groundbreaking discoveries about the function and structure of these crucial components of the segregation machinery.